2011
DOI: 10.3390/s111211157
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms and Soil Pollutants

Abstract: Although the toxicity of metal contaminated soils has been assessed with various bioassays, more information is needed about the biochemical responses, which may help to elucidate the mechanisms involved in metal toxicity. We previously reported that the earthworm, Eisenia fetida, accumulates cadmium in its seminal vesicles. The bio-accumulative ability of earthworms is well known, and thus the earthworm could be a useful living organism for the bio-monitoring of soil pollution. In this short review, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 38 publications
0
28
0
3
Order By: Relevance
“…Earthworms present in an ecosystem have also been shown to decrease the severity of the soil borne bacterial and fungal plant diseases [5,2]. They are also being used as key bio indicator organisms for testing the toxicity of chemicals and pollutants in soil [6,7,8,9,10,11]. Earthworms can be used in waste management, preparation of biofertilizer through vermicomposting, minimization of environmental pollution through vermicomposting, bioaccumulation of toxic residues agrochemicals (metals) and in medicine in the treatment of wound, piles, chronic boils, sore throat, hernia, respiratory ailments, jaundice and rheumatic arthritis [12,3].…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms present in an ecosystem have also been shown to decrease the severity of the soil borne bacterial and fungal plant diseases [5,2]. They are also being used as key bio indicator organisms for testing the toxicity of chemicals and pollutants in soil [6,7,8,9,10,11]. Earthworms can be used in waste management, preparation of biofertilizer through vermicomposting, minimization of environmental pollution through vermicomposting, bioaccumulation of toxic residues agrochemicals (metals) and in medicine in the treatment of wound, piles, chronic boils, sore throat, hernia, respiratory ailments, jaundice and rheumatic arthritis [12,3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that earthworms have a high potential for biological bioremediation of contaminated soils (Suthar et al, 2008;Nahmani et al, 2009;Li et al, 2010;Hirano and Tamae, 2011). These organisms can accumulate a high concentration of heavy metals in the body (Shahmansouri et al, 2005;Li et al, 2010;Brewer and Barrett, 1995;Bamgbose et al, 2000) Based on statistical analysis performed in this study, it was found that, due to the high toxicity of chromium for worms, there was a significant correlation between the concentration of chromium in soil and earthworm mortality, (PV <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that earthworms have a high potential for biological bioremediation of contaminated soils (Suthar et al, 2008;Nahmani, Hodson et al, 2009;Li, Xu et al, 2010;Hirano & Tamae, 2011). However, it has been found that the accumulation of heavy metals in the body of earthworm is partly due to the heavy metal concentrations in soil, Ma et al (1983) reported.…”
Section: Bioremediation Of the Soils Contaminated With Cadmium And Chmentioning
confidence: 99%